2022
DOI: 10.3390/jcm11030896
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Angle Alpha, Angle Kappa, and Optical Aberrations on Visual Outcomes after the Implantation of a High-Addition Trifocal IOL

Abstract: The aim of our investigation was to examine the possible correlations between optical aberrations, angle kappa, angle alpha, and visual outcomes following cataract surgery. In total, 56 eyes of 28 patients were implanted with the Liberty 677MY trifocal intraocular lens (IOL). Pre- and postoperative higher-order aberrations, coma, astigmatism, angle alpha, and angle kappa were registered, along with uncorrected and corrected visual acuities at multiple distances. Visual acuity and contrast sensitivity defocus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
(109 reference statements)
2
20
0
Order By: Relevance
“…and another recent study reported that 42% of eyes had corneal astigmatism of at least 1.00 dioptres (D) [3]. This amount of astigmatism is already large enough to compromise both postoperative visual acuity and visual quality if it is left uncorrected [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…and another recent study reported that 42% of eyes had corneal astigmatism of at least 1.00 dioptres (D) [3]. This amount of astigmatism is already large enough to compromise both postoperative visual acuity and visual quality if it is left uncorrected [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Several multifocal intraocular lenses (IOLs) have been introduced to the market during the last decade. However, the best possible visual outcome can only be accomplished if all refractive errors, including astigmatism, are properly corrected [ 2 , 3 , 4 ]. Ferrer-Blasco et al reported that the majority (87%) of cataract patients had preoperative astigmatism [ 5 ], and another recent study reported that 42% of eyes had corneal astigmatism of at least 1.00 dioptres (D) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with Cervantes-CosteGuadalupe et al [8] who proposed that there is a signi cant difference between postoperative Kappa angle and distant vision, which also reminds us that Kappa angle can be used as one of the factors to predict postoperative distant vision. However, some scholars believe that the distant visual acuity of Kappa angle in trifocal IOL implantation is not affected by central eccentricity, while the lower additional trifocal IOL with slight eccentricity can obtain better near vision, but it will affect the contrast sensitivity [9] .The results of this study suggest that the difference is not statistically signi cant 1 month after operation, which may be related to the recovery of pupil size and the gradual recovery of kappa angle 1 month after operation.…”
Section: Discussionmentioning
confidence: 55%
“…This article showed that among patients with a bifocal IOLs, those with 1.50 D and 2.00 D astigmatism had worse postoperative visual acuity at all distances than those with astigmatisms of 0.00 D and 0.50 D suggesting the need to reduce corneal astigmatism below 1.00 D when implanting a multifocal IOL. Large preoperative corneal astigmatism often limits the application of multifocal IOLs, which results in poor visual acuity at all distances postoperatively 52 . Broadening the types of multifocal IOLs, multifocal IOLs with toric designs have been available since 2007 53 .…”
Section: Discussionmentioning
confidence: 99%